2013
DOI: 10.1111/nph.12597
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase‐mediated early nitric oxide burst alleviates oxidative damage induced by aluminum through enhancement of antioxidant defenses in roots of wheat (Triticum aestivum)

Abstract: SummaryNitric oxide (NO) is an important signaling molecule involved in the physiological processes of plants. The role of NO release in the tolerance strategies of roots of wheat (Triticum aestivum) under aluminum (Al) stress was investigated using two genotypes with different Al resistances.An early NO burst at 3 h was observed in the root tips of the Al-tolerant genotype Jian-864, whereas the Al-sensitive genotype Yang-5 showed no NO accumulation at 3 h but an extremely high NO concentration after 12 h. Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 53 publications
7
135
0
Order By: Relevance
“…Both enzymes activity could be helpful in improving the tolerance of wheat plants to Pb-toxicity. It is reported that NR induced nitric oxide (NO) synthesis that protects plants against abiotic stress (Sun et al, 2014;Khan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both enzymes activity could be helpful in improving the tolerance of wheat plants to Pb-toxicity. It is reported that NR induced nitric oxide (NO) synthesis that protects plants against abiotic stress (Sun et al, 2014;Khan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The burst of NO as a cell-signaling molecule during metal treatment reflects the specific role of NO in plant response to metal stress. For instance, in many reports of NO production found in plants under metal stress, NO was suggested to have an important protective effect on plant cells against metal toxicity (Kazemi 2012;Sun et al 2014;Yu et al 2012;Zhou et al 2012). However, the enhanced stress signal might be a result of higher levels of NO acting as a negative regulator of the resistance response in plants against metals.…”
Section: Discussionmentioning
confidence: 97%
“…Metals treatment alters NO concentrations in plants. It has been widely reported that NO contents significantly increased in plants exposed to metal treatments, including Al (Sun et al 2014), Cd (Alemayehu et al 2015;Ye et al 2013), Zn (Xu et al 2010b), Ni (Kazemi 2012), Pb (Yu et al 2012) and As (Singh et al 2009). However, metal stress can also decrease NO accumulation; for example, in the roots of rice (Xiong et al 2009) and Medicago truncatula (Xu et al 2010a) after treatment with Cd.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations